Repurchase Intention at Miniso: The Impact of Price and Appearance Perception with Brand Experience Mediation - Rahmadini, Shelsy Sri; Thabrani, Gesit (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
A key issue for businesses today is maintaining and enhancing consumers’ intentions to repurchase. As a result, repurchase intention has become a critical topic of study. This research examines the impact of price perception and appearance perception on repurchase intention, with brand experience acting as a mediating variable, using Miniso in Padang City as the research context. Data were collected using a convenience sampling technique through an online questionnaire distributed via Google Forms, yielding 180 valid responses. The data analysis was performed with Smart PLS version 4.0. The results indicate that perceptions of price, product appearance, and brand experience each have a significant influence on consumers' repurchase intentions. Furthermore, brand experience plays a mediating role in the relationships between both price and appearance perception and repurchase intention. The findings of this study support consumer behavior theory, highlighting that consumers’ evaluations of price and product appearance affect their repurchase decisions, which are further strengthened by their brand experience.